The right of publicity privacy reimagined for a public world - Rothman, Jennifer E., 1969- (Harvard University Press, 2018)
The Right of Publicity: Privacy Reimagined for a Public World provides the first serious scholarly analysis of an increasingly important legal claim--the right of publicity. This unwieldy law, often the darling of celebrities, protects against the use of a person's identity without permission. Often erroneously thought to have been created in the 1950s, the law has expanded into a new type of intellectual property right that limits free speech and interferes with authors' use of copyrighted works. Most troublingly, the right of publicity now threatens to undermine the very rights of the individuals it was designed to protect. By revisiting the real story of how the right of publicity came to be what it is today, the author provides a path forward for limiting the right. The book tackles a host of current issues, from the use of celebrities' images on merchandise and in social media, to claims by student-athletes that they should be paid when their likenesses appear in videogames and photographs, to the objections of subscribers to the use of their names and images in sponsored advertisements in social media, to efforts to get one's image and name removed from revenge porn and mugshot websites, to the taxation and control of dead celebrities' lucrative identities.--